Peponium elgonense (Cucurbitaceae), a new species from Mount Elgon in Kenya - Mutie, Fredrick Munyao; Rono, Peninah Cheptoo; Kathambi, Vivian; Wei, Neng; Kamau, Peris; Gituru, Robert Wahiti; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2020)
Peponium elgonense, a new species of Cucurbitaceae from Mount Elgon in Kenya, is described and illustrated here with photographs. This species is similar to P. cienkowskii and P. vogelii, but differs by being monoecious and having a longer ovary. A molecular phylogenetic analysis of Peponium based on ITS and five plastid markers (trnL–F, rpl20–rps12, matK, rbcL, and trnL intron) of four species of Peponium further shows that P. elgonense individuals cluster together supporting the argument to regard it as a separate species.